Pemanfaatan Teknologi Canva dalam Meningkatkan Efektivitas Pembelajaran Pendidikan Pancasila di SD Negeri 01 Watusalam - Taufik Afandi; M. Ali Ghufron (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
In the digital era, learning Pancasila Education at SD Negeri 01 Watusalam faces challenges in delivering material that is interesting and easy for students to understand. This research aims to examine the use of the Canva graphic design application in increasing the effectiveness of Pancasila education learning in the school. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research results show that using Canva in learning can increase students' creativity, allowing them to create more interesting and interactive learning materials, such as posters and infographics, which help them understand the values ​​of Pancasila better. Apart from that, using Canva also increases student involvement and motivation in the learning process. However, this research also identified several limitations, such as limited access to technological devices and stable internet connections, as well as a lack of training for teachers in using graphic design applications such as Canva. However, with the right guidance and optimal use, Canva can be an effective tool for improving student learning outcomes and developing graphic design skills relevant to the needs of today's digital world. This research recommends the need for training for teachers in using Canva and improving technology infrastructure in schools to support digital-based learning.